BCG vaccination induced protection from COVID-19 (2020)
There are worldwide urgency, efforts, and uncertainties for the discovery of a vaccine against SARS CoV2. If successful, it will take own time till useful for the humans. Till the specific vaccine available, there are evidences for repurposing existing other vaccine. It is observed that the countries having routine BCG vaccination programme, had shown to have lower incidence of COVID19, suggesting some protective mechanisms of BCG against COVID-19 in such countries. Countries like India despite vast population density and other adversities, and growing numbers of COVID19 infections, the mortality rate and severity of COVID has been low in comparison to TB non-endemic countries (like Europe and USA). In addition, there are evidences that BCG vaccination offers partial protection and survival in low-income countries where tuberculosis is prevalent. The nonspecific effects (NSEs) of immune responses induced by BCG vaccination, protect against other infections are seems to be due to its immunological memory eliciting lymphocytes response and trained immunity. The protective effect on other viral infection in humans are believed to be mediated by heterologous lymphocyte activation and the initiation of innate immune memory may be applicable to SARS CoV2. The BCG vaccination at birth does not have protective effect beyond childhood against COVID-19. In adult, there might be some other factors dampening the virulence and pathogenicity of COVID-19. In the TB endemic countries like India, with high population density, similar to BCG vaccination, the environmental Mycobacteria might be imparting some immune-protection from severity and deaths of COVID-19.